A Proposed Surface Area Measurement Module for Rural Folks: Desing Concept and trial Setup - Pattarapaprakorn, Woraratana; Tono, Makoto; Niyama, Hiro (ASEAN Journal of Chemical Engineering, 2004)
A simple module for surface area measurement based on CO2 adsorbtion.at dry-ice methanol temperrature was designed. The designed consists a sample tube, a glass syiringe for pressure measurement, and an anspirator for evacuation. No shopiscate electronic de w used. Dry ice was used Dry ice was coolent in place of liquid nitrogen, which is widely wed in ordinary BET surface area measument. Vacuum tighess w confied acceptable when cooking oil was used a seal liquid at the contact suace of the singe. Error anaIes were done for both vacuum tighness and the prence of riduaI gases due to the use of water-driven aspiration. Adsorbtion measurements of CO2 were conducted using the simple module and a conventional apparatus. Results confirmed that the modue works well within reasonable eximental error, if the weight of sampIe and the initial intake of sample gas are chosen properly. However since the adsorption isotherms of several carbon samples shawed a pleteau at high preure, the BET equation was not applicble. Instead, the Langmuir one-point method would be rocommended for surface area mesurement.